I Eat Therefore I Believe: The Raw Food Diet, a Believing Solution for Healing - Thircuir, Solenn (The international journal of religion and spirituality in society, 2019)
As Alan Levinovitz argued, food can be an entry point into the study of religion. In this sense, how does religiosity manifest itself in the raw food diet? This food practice is based on the idea of finding salvation, but for this to happen, one must find its nature. The raw food leaders promise a revolutionary diet that could cure disease and guarantee the return to Adam and Eve’s natural paradise. By condemning a cultural symbol such as cooking, they claim to have the key to escape the degenerative modernity. They seduce and convert a cult of followers in Western countries. The dichotomies on which the norms of this diet are based refer to the notions of the pure and the impure, of the good and the bad. They divide up the world according to moralistic binaries. This article aims to analyze the raw food diet values and how a myth is constructed by the updating of religious foundations where love for nature and believing in the power of certain foods can be considered as a religion.